Innovative ways to teach the life and work of Rashod Nuri Guntekin in literary education - Saburova Qunduz Erkebay qizi; Hamza Allambergenov (Peerian Journals Publishing, 2023)
This article analyzes modern methods of teaching the famous Turkish writer Rashod Nuri Guntekin`s work „Cholikushi“ in literary education
Keywords: Method; opportunity; interactive method; communication